Incidences of Hypothyroidism Associated With Surgical Procedures for Thyroid Disorders: A Nationwide Population-Based Study - Tsai, Shin-Han; Chien, Shuo-Chen; Nguyen, Phung-Anh; Chien, Po-Han; Ma, Hon-Ping; Asdary, Rahma Novita; Wang, Yao-Chin; Humayun, Ayesha; Huang, Chen-Ling; Iqbal, Usman; Jian, Wen-Shan (Frontiers in Pharmacology, 2019)
Background and aim: Limited information available about different types of thyroid surgeries with risk for postoperative hypothyroidism. This study aimed to investigate the risk of developing early and late-onset postoperative hypothyroidism in patients with thyroid disorders. Methods: We used a large cohort data from the Taiwan National Health Insurance Research Data Base (NHIRDB) and identified 9,693 (9,348) patients from January 1998 to December 2010, admitted for thyroid disorder surgeries. We used the surgical procedures time as the index date. Our observational retrospective cohort study excluded the subjects diagnosed with hypoparathyroidism and hypothyroidism before any surgeries. We analyzed the data using the Cox regression model to calculate the hazard ratio. Result: Postoperative hypothyroidism associated with bilateral-total (HR, 4.27; 95% CI, 3.32 to 5.50), one-side total and another subtotal (HR, 3.16; 95% CI, 2.59 to 3.86), bilateral-subtotal (HR, 1.65; 95% CI, 1.37 to 1.98) and unilateral-total (HR, 1.17; 95% CI, 0.95 to 1.44) surgical procedures. The time intervals for thyroid disorders were 320 cases developed postoperative hypoparathyroidism in eight weeks, 480 cases the second month, and 1000 cases in the first year after surgery. Conclusion: Findings suggest that thyroidectomy was associated with transient postoperative hypothyroidism in thyroid disorder patients. The bilateral-total surgical procedure was strongly associated with temporary postoperative hypothyroidism.